Role of syntrophic microbial communities in high-rate methanogenic bioreactors - Stams, Alfons Johannes Maria (2012)
Anaerobic purification is a cost-effective way to treat high strength industrial wastewater. Through anaerobic treatment of wastewaters energy is conserved as methane, and less sludge is produced. For high-rate methanogenesis compact syntrophic communities of fatty acid-degrading bacteria and methanogenic archaea are essential. Here, we describe the microbiology of syntrophic communities in methanogenic reactor sludges and provide information on which microbiological factors are essential to obtain high volumetric methane production rates. Fatty-acid degrading bacteria have been isolated from bioreactor sludges, but also from other sources such as freshwater sediments. Despite the important role that fatty acid-degrading bacteria play in high-rate methanogenic bioreactors, their relative numbers are generally low. This finding indicates that the microbial community composition can be further optimized to achieve even higher rates.